Carotid Arterial Compliance and Aerobic Exercise Training in Chronic Traumatic Brain Injury: A Pilot Study. Issue 5 (23rd September 2022) - Tomoto, Tsubasa; Le, Tran; Tarumi, Takashi; Dieppa, Marisara; Bell, Kathleen; Madden, Christopher; Zhang, Rong; Ding, Kan
Abstract : Objective: Decreased carotid arterial compliance (CAC) is associated with cerebral microvascular damage, cerebral blood flow (CBF) dysregulation, and increased risk for stroke and dementia, which are reported to be prevalent after traumatic brain injury (TBI). However, the effect of TBI on CAC has not been reported. The purposes of this pilot study were to (1) compare CAC between participants with chronic traumatic brain injury (cTBI) and age-matched healthy control (HC) subjects and (2) to examine whether CAC changed after 3 months of exercise training in those with cTBI. Setting: Community based. Participants: Nineteen participants with cTBI (6-72 months postinjury) and 19 HC matched for age and sex were tested at baseline. The same cTBI cohort was enrolled in a proof-of-concept randomized controlled exercise training program to investigate the effects of 3 months of aerobic exercise training (AET) or nonaerobic stretching and toning (SAT) on cerebrovascular parameters. Design: Cross-sectional study and randomized controlled trial. Main Measures: CAC was measured by tonometry and ultrasonography at the common carotid artery; CBF was measured by ultrasonography at the bilateral internal carotid and vertebral arteries, and pulsatile CBF was measured by transcranial Doppler ultrasonography at the middle cerebral arteries. Cerebrovascular resistance (CVR) was calculated as mean arterial pressure divided by total CBF. Results: Relative to HC, the participants with cTBI had lower CAC (0.10 ± 0.03 vs 0.12 ± 0.03 mm 2 /mm Hg, P = .046) and higher CVR (0.17 ± 0.03 vs 0.15 ± 0.03 mm Hg/mL/min, P = .028). CAC tended to increase after AET compared with SAT ( P = .080). Increases in CAC were associated with decreased pulsatile CBF ( r = −0.689, P = .003). Conclusion: These findings suggest that the individuals with cTBI have decreased CAC, which may potentially be improved by AET.